Effect of ration balancing on methane emission, faecal archaeol concentration and its relation to enteric methane in crossbred cows - GARG, M G; SHERASIA, P L; PHONDBA, B T (The Indian Journal of Animal Sciences, 2014)
A field study was conducted to evaluate the effect of ration balancing on methane emission, faecal archaeol and its relation with enteric methane in crossbred cows. Crossbred cows (25) in their early stage of lactation (60–80 d postpartum) were identified under field conditions. After recording their average daily feed intake and milk yield for 1 week, methane emission was measured by SF6 tracer technique. A balanced ration was worked out for individual cows and fed to them for 30 d. After feeding a balanced ration, feed intake and methane emission was measured again. On feeding a balanced ration, methane emission (g/d) was reduced by 10.1%. Archaeol concentration in faeces being considered as an indicator of methane emission, its concentration in faeces was measured before and after feeding a balanced ration, which reduced significantly. There existed a significant correlation (r=0.12) between methane emission measured by SF6 tracer technique (g/d) and archaeol concentration (mg/kg DM of faeces). However, more data need to be generated in this regard.